Analisis Yuridis Perlindungan HAM Terhadap Tindak Represif Aparat Dalam Aksi Demo Mahasiswa Di Gedung DPR - Qaulan Sadidah; Selly Patria Amanda (Jurnal Kajian Hukum dan Pendidikan Kewarganegaraan, 2025)
The repressive actions of the police in handling student demonstrations at the DPR building have often resulted in violations of human rights (HAM). Demonstrations are essentially a manifestation of the constitutional rights of citizens guaranteed under Article 28E of the 1945 Constitution of the Republic of Indonesia. However, in practice, the authorities frequently employ excessive force. The purpose of this research is to identify the forms of legal protection for students in exercising their right to express opinions and to analyze why repressive actions by law enforcement officials can be categorized as human rights violations. This study applies a normative juridical method with statutory and conceptual approaches, examining the 1945 Constitution, the Criminal Procedure Code (KUHAP), the Criminal Code (KUHP), as well as relevant police regulations. The findings reveal a significant gap between the legal framework and actual practices in the field, where law enforcement officers continue to carry out repressive measures that undermine students’ freedom of expression.